2017
DOI: 10.1038/srep45223
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Osteoarthritis in Mice Following Mechanical Injury to the Synovial Joint

Abstract: We investigated the spectrum of lesions characteristic of post-traumatic osteoarthritis (PTOA) across the knee joint in response to mechanical injury. We hypothesized that alteration in knee joint stability in mice reproduces molecular and structural features of PTOA that would suggest potential therapeutic targets in humans. The right knees of eight-week old male mice from two recombinant inbred lines (LGXSM-6 and LGXSM-33) were subjected to axial tibial compression. Three separate loading magnitudes were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…We have recently shown that mice develop ectopic calcifications (i.e., calcified nodules in and around the synovium) after surgical DMM or mechanical loading . In the present study, we quantified these nodules after joints were scanned by micro‐CT scanner as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that mice develop ectopic calcifications (i.e., calcified nodules in and around the synovium) after surgical DMM or mechanical loading . In the present study, we quantified these nodules after joints were scanned by micro‐CT scanner as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…One major advantage of this method is that the traumatic load must only be applied a single time to produce the desired results. Rai et al utilized this method to study the pathophysiology of OA in mice and found the progression of the disease to be similar to, albeit faster than, the progression of the disease in humans [52]. Based on the results of their study, they identified chondrocyte apoptosis, synovitis, and ectopic calcification as possible targets for therapeutic interventions [52].…”
Section: Non-invasive Induced Modelsmentioning
confidence: 99%
“…Naturally occurring X X X X [9][10][11] Genetically modified X X X X [12][13][14][15][16][17][18][19][20][21][22][23][24] Surgically induced (all) X X X X X [25][26][27][28][29][30] Chemically induced (all) X [31][32][33][34][35][36][37][38][39] Non-invasive induction X X X X X [40][41][42][43][44][45][46][47][48][49][50][51][52] [5,8,63,64]…”
Section: Referencesmentioning
confidence: 99%
“…In the last 10 years, multiple non‐invasive ACL rupture models have been developed. These models have primarily used mice and rabbits, with a limited number of studies involving rats . Despite being relatively understudied, there are advantages to establishing this injury model in rats, such as their amenability to behavioral tests and their larger size, which can accommodate certain imaging modalities and therapeutic interventions .…”
mentioning
confidence: 99%